PHYTOCHEMICAL AND ANTIOXIDANT INVESTIGATIONS OF A CLAUSENA ANISATA HOOK, A SOUTH AFRICAN MEDICINAL PLANT - Lawal, Ibraheem Oduola; Grierson, Don S; Afolayan, A J (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Clausena anisata (Willd). Hook (Rutaceae), also known as Iperepesi in Xhosa language is a medicinal plant widely used by herbalists for the treatment and/or management of several ailments such as chronic cough, tuberculosis and lung ulceration in Eastern Cape, South Africa. With reference to the information gathered in our previous study, we investigated the plant’s phyto-constituents, as well as its inhibitory effects using aqueous and two different organic solvent of extractions in order to justify its folkloric usage. Methods: Antioxidant activity of the plant was screened through 1,1- diphenyl-2-picrylhydrazyl (DPPH), 2,2’-azino-bis(3-ethylbenzthiazoline-6- sulfonic acid) (ABTS) diammonium salt, nitric oxide (NO), and ferric reducing power. Total phenols, flavonoids, flavonols, proanthocyanidins, tannins, alkaloids and saponins were investigated using spectroscopic techniques. Results: There were no significant differences in the flavonoid and proanthocyanidins contents between the leaves and bark extracts of C. anisata respectively, while the total phenolic content of the bark extract of C. anisata was significantly higher than that of the C. anisata leaf. The acetone extracts of both the leaf and bark indicated strong antioxidant activities. Conclusion: The observed activities of the plant extracts could be attributed to the high contents of the phenolics, alkaloids, flavonoids, saponins, proanthocyanidins and tannin. The acetone extracts of the plants have also exhibited strong antioxidant activities in vitro. It has been established scientifically that oxidative stress is linked with several degenerative conditions and diseases; the inhibitory effects of these plant extracts on the free radicals could logically justify the folkloric usage of C. anisata leaf and bark in the Eastern Cape for the treatment of respiratory infection diseases.